Private cloud bespoke orchestrator: techniques for constructing and operating bespoke-private cloud virtual machine environments for cloud users - Joonseok Park; Sumin Jeong; Keunhyuk Yeom (Journal of Cloud Computing: Advances, Systems and Applications)
Abstract With the emergence of the cloud computing paradigm, private clouds have become critical components of hybrid and multi-cloud environments. However, there is a lack of practical support technologies and methodologies for constructing virtual machines when adopting private clouds. This study proposes a private cloud bespoke orchestrator (PCBO) for constructing and operating private cloud virtual machine environments. The proposed PCBO supports the construction of automated virtual machine environments in private clouds and provides techniques for supporting the recovery of virtual machines. Additionally, this paper presents a case study on applying the proposed PCBO to the open-source cloud computing platform OpenStack, which can be used to build both private and public clouds. It is anticipated that the techniques proposed in this paper will serve as foundational reference technologies for constructing and operating private cloud virtual machines and handling failures as they occur.